Indigenous Herbal Drug (Tinospora Cordifolia) Induced Liver Injury: A Case Report - Sounak Kumar Roy; Muniruddin SK; Subham Mondal; Sandipan Mukherjee; Santa Subhra Chatterjee (Bengal Physician Journal)
Drug-induced liver injury (DILI) is a condition characterized by acute or chronic liver damage following the use of hepatotoxic drugs. It can be classified based on clinical presentation (hepatocellular, cholestasis, or mixed), mechanism of hepatotoxicity, or histological appearance. Drug-induced liver injury also includes cases related to herbal-induced liver injury (HILI). Diagnosing DILI requires excluding other potential causes and identifying a consistent pattern of liver involvement. The pathogenesis typically involves the parent drug or its metabolites, which may directly impact cell biochemistry or trigger an immune response. The specific drug involved influences the pattern of liver function abnormalities, the latency period before symptom onset, the presence of immune-mediated hypersensitivity, and the response to drug discontinuation. The case discussed illustrates a DILI caused by an indigenous herbal drug, highlighting the complexities of identifying and managing liver injury in such scenarios.